Os currículos do curso de educação física nas instituições públicas do estado de São Paulo - Custodio, Vanessa (Universidade Federal de São Carlos, 2018)
This research aims to verify the effectiveness, as a measure of public policy performance, of the curricular grades of the higher education public institutions that train physical education professionals. The career of multidisciplinary aspect has foreseen in its curricular guidelines the ability to manage resources and design programs and projects as well as work in multi-professional teams, besides teaching, research, physical and sporting training, deeper assignments. Therefore, it will be presented the paths of the physical education professional's profile construction as well as studies on public policy research and what parameters evaluate the performance of these policies. Lastly, the curricular grades will be decomposed in categories for the analysis of content and discussion about the public policy of the physical education professional training according to what is established in the National Curricular Guidelines and in the Brazilian College of Sports Sciences.
Keywords: Formação profissional; Educação física; Políticas públicas; Efetividade; Professional qualification; Physical education; Public policy; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS